2019
DOI: 10.1103/physrevlett.123.020403
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and Asymmetry Cannot be Broadcast

Abstract: In the presence of conservation laws, superpositions of eigenstates of the corresponding conserved quantities cannot be generated by quantum dynamics. Thus, any such coherence represents a potentially valuable resource of asymmetry, which can be used, for example, to enhance the precision of quantum metrology or to enable state transitions in quantum thermodynamics. Here we ask if such superpositions, already present in a reference system, can be broadcast to other systems, thereby distributing asymmetry indef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 44 publications
4
50
0
Order By: Relevance
“…Throughout we adapt a resource-theoretic approach to quantum thermodynamics called thermal operations [27,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. This is a wellestablished framework for studying thermodynamic processes in the quantum regime which gives the experimenter the most freedom in manipulating systems without access to external resources like coherence or asymmetry [25,[46][47][48][49], entanglement [50][51][52] or conserved quantities [53][54][55]. It is thus a convenient class of operations for deriving fundamental thermodynamic limitations.…”
Section: Frameworkmentioning
confidence: 99%
“…Throughout we adapt a resource-theoretic approach to quantum thermodynamics called thermal operations [27,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. This is a wellestablished framework for studying thermodynamic processes in the quantum regime which gives the experimenter the most freedom in manipulating systems without access to external resources like coherence or asymmetry [25,[46][47][48][49], entanglement [50][51][52] or conserved quantities [53][54][55]. It is thus a convenient class of operations for deriving fundamental thermodynamic limitations.…”
Section: Frameworkmentioning
confidence: 99%
“…Quantum coherence and correlations require a cost of production as they are resources [98,99], which should be adequately translated to the first and second laws of quantum thermodynamics in the case of quantum coherent or correlated systems [100]. Even catalytic use of coherence has been argued to be limited fundamentally [101,102]. By identifying quantum thermal operations and their resource theoretic descriptions, fundamental bounds on quantum information-thermal engines have been provided [103].…”
Section: Family Of Second Laws Is Expressed In Terms Of Inequalities mentioning
confidence: 99%
“…It can be shown that coherence does not increase under strictly energy preserving operations, that is, operations that commute with the system Hamiltonian. However, by allowing correlations to build up, it is possible to put an arbitrary number of systems into approximate coherent superpositions with the help of an infinite-dimensional reference system acting as a catalyst [29,30,48] 2 . In this work, we are interested in a variation of this coherence 'catalysis' in which an optical coherent state acts as our reference system.…”
Section: Coherence As a Resourcementioning
confidence: 99%